(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to describe the knowledge and attitudes of nursing students at Dai Nam University towards scientific research in 2024 and identify related factors. Subject and method: A cross-sectional study was conducted on 200 nursing students from April to July 2024. Results: Results showed that only 19% of students had adequate knowledge of scientific research, and merely 10.5% exhibited a positive attitude. Factors influencing knowledge included age, academic year, lecturer encouragement, participation in research groups/clubs, access to scientific information, and plans for postgraduate studies. Attitudes were similarly influenced by these factors, along with information-seeking skills and participation in research projects. Conclusion: The low percentage of students with adequate knowledge and positive attitudes toward scientific research. The findings suggest a need for adjustments in the university’s educational programs and policies to improve students’ knowledge and attitudes towards scientific research.